THE RELATIONSHIP BETWEEN THE DURATION OF HEMODIALYSIS AND BODY MASS INDEX IN CHRONIC KIDNEY DISEASE PATIENTS AT SANJIWANI HOSPITAL - Darmadi, I Gusti Ayu Maha Deivy; Sutadarma, I Wayan Gede; Tianing, Ni Wayan; Surudarma, I Wayan (E-Jurnal Medika Udayana; Vol 14 No 4 (2025): E-Jurnal Medika Udayana, 2025)
Chronic kidney disease (CKD) occurs when kidney function declines, as indicated by a glomerular filtration rate (GFR) below 60 mL/min/1.73 m² for 3 months or more. Hemodialysis is used to replace the lost kidney function. However, long-term hemodialysis can worsen the nutritional status of patients. Body mass index (BMI) is a good non-invasive indicator for assessing nutritional status. The purpose of this study is to determine the relationship between the duration of hemodialysis and BMI in CKD patients at Sanjiwani Hospital. This analytical observational study used a cross-sectional approach involving 95 CKD patients undergoing hemodialysis at Sanjiwani Hospital who met the inclusion and exclusion criteria. The relationship between the duration of hemodialysis and BMI was analyzed using the Spearman correlation test. The study subjects were predominantly male (63.2%), with a median age of 50 years (range: 21-63 years). The median duration of hemodialysis was 3 years (range: 1-17 years). The mean BMI was 24.15 ± 4.56 kg/m². The analysis showed a significant relationship between the duration of hemodialysis and BMI (r = -0.211, p = 0.04). This study concludes that there is a weak but significant negative correlation between the duration of hemodialysis and BMI, with a tendency for longer hemodialysis duration to be associated with a decrease in BMI.